Digital mapping of the urinary bladder: potential for standardized cystoscopy reports - Kriegmair, Maximilian; Ritter, Manuel; Michel, Maurice Stephan (Urology, 2017)
Objective to develop a standardized digital reporting tool for cystoscopy of the urinary bladder using panoramic imaging. Materials and Methods: An image processing and stitching software (Endorama) was developed to generate panoramic images from cystoscopy data. In a processing phase, algorithms were modulated and refined by reference to cystoscopy sequences (n = 30). Subsequently, standard systematic cystoscopies (n = 12) were recorded in patients undergoing transurethral resection of a bladder tumor to create panoramic images. Results: All sequences were applicable for the development and refinements of the software. Processing increasingly allowed the creation of images illustrating large parts of the bladder and relevant anatomic landmarks in different locations. The pathway covered by the endoscope during the intervention was illustrated as a route in the respective digital image. During the application phase, panoramic images were successfully created in 10 out of 12 cases. The resolution of the images was 4096 × 2048 pixels and the images required a median digital memory of 3.9 MB (3.4-5.7). The panoramic images illustrated 22 relevant findings of which 7 were papillary tumors. Conclusion: High-quality digital panoramic maps of the urinary bladder were created using specifically processed data of videocystoscopy. In this preliminary series, relevant findings were illustrated in the respective image. Our tool may help improve standardization of cystoscopy reports and reduce interobserver variability.